Counter-Examples in Linguistics (Science): The Case of Circassian as a Split Anaphor Language - Colarusso, John (Linguistica Atlantica, 2004)
Linguists often resist data that undermines the dominant paradigm to which they adhere. This paper examines split anaphors in Circassian, a language of the Caucasus, as a case study of such rejection. A typology of counterexamples is devised and contrastively applied to physics and to linguistics, with etTortsmade to cite examples from each field. The split anaphor case is presented as an error in prediction and hence as a refutation of the Government and Binding paradigm. Its treatment is contrasted with that of the orbit of Mercury, a comparable error in prediction of Newtonian mechanics. A symmetry-breaking approach is taken to the problem of split anaphor (in which reflexivesare ergative while reciprocals are anti-ergative).A new explanation for ergativity is offered. This explanation predicts that only ergative languages with a particular rule coupling will exhibit split ergativity